Progression independent of relapsing biology in multiple sclerosis: a real-word study - Yong, Heather Y. F.; Camara-Lemarroy, Carlos (Frontiers in Neurology, 2025)
Progression independent of relapse activity (PIRA) implies disability progression in people with relapsing–remitting multiple sclerosis (RRMS) secondary to neurodegeneration. Mechanistically and biologically PIRA could impact the traditional distinction between progressive and relapsing-MS. Herein, we estimated progression independent of relapsing biology (PIRB) in a cohort of 823 participants with clinically-isolated syndrome/RRMS in Calgary, Canada using a modified criterion [excluding relapses, inflammatory MRI activity, interim disability worsening/improvement over the observation period, and progression secondary to alternative causes including formal conversion to secondary-progressive MS]. PIRB was rare and rates remained consistent across disease-modifying therapies (3.75% dimethyl fumarate, 3.67% fingolimod, 3.72% ocrelizumab, 3.52% minocycline) despite varied rates of disability progression. PIRB may offer a practical alternative to the concept of PIRA.